PENDIDIKAN AGAMA, ANTARA KESEJAHTERAAN DUNIAWI DAN KEBAHAGIAAN UKHRAWI - H. Abd. Muqit (Universitas Islam Madura, 2019)
Religious education, between world welfare and ukhrawi happiness, as understood together that Islam provides guidance and direction to all humanity in all sectors of life, worldly life is no problem to be pursued in all its dimensions, only needs to be directed and used according to the religious rules , by means of forgiveness and abandoning evil ways, so that the welfare of the world obtained will lead to happiness hereafter. In Islam is the balance of worldly and ukhrawi orientation, not neglecting one of them let alone defeat it. This is not easy, so religious education is an important and necessary thing as a guide and media that directs humans to become educated and devoted beings. With education and devotion, humans will easily get and reach the welfare and happiness of the world and the hereafter.